Electromagnetic shielding, wicking, and drying characteristics of CSP/AN/SSW hybrid yarns-incorporated woven fabrics. (September 2016) - Yu, Zhi-Cai; He, Hua-Ling; Lu, Yan-Hua; Lu, Xin; Zhang, Jian-Fei; Lou, Ching-Wen; Lin, Jia-Horng
To improve the wearing comfort, durability, and antibacterial properties of the electromagnetic (EM) shielding property, a type of multifunction EM shielding woven fabrics which having great liquid transport and drying ability were fabricated in this study. This study aims to investigate theirs liquid transport, drying, and electromagnetic (EM) shielding properties. For this purpose, initially six types of multifunctional crisscross-section polyester (CSP)/antibacterial nylon (AN)/stainless steel wire (SSW) metal hybrid yarns with different wrapping amounts were produced using hollow spindle spinning technique. Conductive woven fabrics were then woven with CSP/AN/SSW metal hybrid yarns as weft yarns, and PET filaments as the warp yarns. The liquid transport and drying ability of the conductive woven fabrics were evaluated in terms of wicking ability and water evaporation rate, which are two vital factors that affect the physiological comfort level of personal protective clothing (PPC). Results indicated that adding CSP yarn in the fabricated EM shielding woven fabric could obviously improve the drying rate of the fabric. The EM shielding behavior of these woven fabrics were analyzed using a vector network analyzer in the frequency range of 300 kHz–3 GHz. Results showed that the wrapping amounts of the metal hybrid yarns significantly affect the wicking and drying abilities of the woven fabrics. In addition, the lamination angles of the fabrics with different amounts of layers remarkably affect their EM shielding characteristics.